Marketing Mix Analysis of Consumer Satisfaction at Rumah Bibit Parepare - Irmayani, Irmayani; Yusran, Yusran; Nurhaedah, Nurhaedah (Penerbit Goodwood, 2025)
Purpose: This study aimed to determine the effect of the marketing mix (Product, Price, Promotion, and Place) on consumer satisfaction at Rumah Bibit Pare, a business specializing in horticultural plant seeds. Methodology/Approach: This research uses a quantitative descriptive approach with data collected through questionnaires, interviews, observations, and documentation. Data analysis was performed using multiple linear regression analysis. Results/Findings: The product had a positive effect on consumer satisfaction. Price has a positive effect on consumer satisfaction. Place does not positively affect consumer satisfaction. Promotions do not have a positive effect on consumer satisfaction. The combination of Product, Price, Place, and Promotion has a positive effect on consumer satisfaction. Conclusions: The study concludes that Product and Price are significant factors influencing consumer satisfaction at Rumah Bibit Pare, while Place and Promotion do not show a significant effect. The marketing mix variables positively affect consumer satisfaction. Limitations: This study is limited by its focus on Rumah Bibit Pare and may not be generalizable to other businesses in the horticultural seed industry. Contribution: This research provides practical insights for businesses in the horticultural sector to optimize their marketing strategies, particularly focusing on Product and Price to enhance consumer satisfaction.